PENGGUNAAN PROGRAM UNGGULAN KEAGAMAAN DALAM STRATEGI PENCITRAAN MEREK SEKOLAH ISLAM MODERN - Ayu Saputri, Dinda; Izzah, Nailul; Huwaida, Nisrina; Khairul Anam, Rifqi (As-Sulthan Journal of Education, 2026)
This study aims to analyze how the concept of branding is applied in the context of modern Islamic educational institutions and how religious excellence programs contribute to building the school’s image and strengthening public trust. Branding in modern Islamic schools is not merely a promotional tool but a strategic effort to reflect Islamic values integrated with scientific and technological advancement. Programs such as Qur’an memorization (Tahfizh), bilingual education, and Islamic character development serve as distinguishing features that define the identity of modern Islamic schools. The findings indicate that the effectiveness of religious programs significantly influences public interest and parental trust in these institutions. The success of branding in modern Islamic education is determined by the consistency between claimed values, professional program implementation, and tangible results in shaping students’ character. Therefore, modern Islamic schools successfully integrate spirituality, intellectuality, and modernity, making them trusted and preferred institutions within society.